2019
DOI: 10.3390/microorganisms7110497
|View full text |Cite|
|
Sign up to set email alerts
|

Bioremediation of Artificial Diesel-Contaminated Soil Using Bacterial Consortium Immobilized to Plasma-Pretreated Wood Waste

Abstract: Bioaugmentation is a bioremediation option based on increasing the natural in-situ microbial population that possesses the ability to degrade the contaminating pollutant. In this study, a diesel-degrading consortium was obtained from an oil-contaminated soil. The diesel-degrading consortium was grown on wood waste that was plasma-pretreated. This plasma treatment led to an increase of bacterial attachment and diesel degradation rates. On the 7th day the biofilm viability on the plasma-treated wood waste reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Our findings also prove that inoculation using pre-selected isolates with the ability to metabolize both n-alkanes and PAHs is a better option than the enrichment approach for bioremediation, although solutions like the immobilization of bacterial cells may increase the degradation rate of hydrocarbons [59,60]. Most PAHs, as well as n-alkanes, were degraded most efficiently in the BA-C2 microcosms.…”
Section: Discussionsupporting
confidence: 56%
“…Our findings also prove that inoculation using pre-selected isolates with the ability to metabolize both n-alkanes and PAHs is a better option than the enrichment approach for bioremediation, although solutions like the immobilization of bacterial cells may increase the degradation rate of hydrocarbons [59,60]. Most PAHs, as well as n-alkanes, were degraded most efficiently in the BA-C2 microcosms.…”
Section: Discussionsupporting
confidence: 56%
“…This is because more than one bacterial species is required to efficiently degrade TPH, as no single microbial species can metabolize the complex mixture of petroleum [ 8 ]. A possible option to improve soil bioaugmentation is to add a substrate that allows P. fluorescens to form biofilms; in previous studies, it has been observed that the implementation of substrates increases the formation of biofilms of P. putida , improving the bioremediation of polluted soil [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive characterization of microbial functional diversity is essential for a better understanding of contaminated site bioremediation [19][20][21]. However, most studies on azo dye degradation focused on isolation, identification, and characterization of culturable bacteria [22,23]. It is estimated that only 0.1-1% microorganisms are culturable using conventional methods.…”
Section: Introductionmentioning
confidence: 99%